Multicentre evaluation of dengue IgM dot enzyme immunoassay - Lam, S.K.; Fong, M.Y.; Chungue, E.; Doraisingham, S.; Igarashi, A.; Khin, M.A.; Kyaw, Z.T.; Nisalak, A.; Roche, C.; Vaughn, D.W.; Vorndam, V. (1996)
Background: The traditional methods used in the diagnosis of dengue infection do not lend themselves to field application. As such, clinical specimens have to be sent to a central laboratory for processing which invariably leads to delay. This affects patient management and disease control. The development of the dengue IgM dot enzyme immunoassay has opened up the possibility of carrying out the test in peripheral health settings. Objectives: This multicentre study was conducted to evaluate a new, commercial nitrocellulose membrane based IgM capture enzyme immunoassay. Study design: The sensitivity and specificity of the test were compared with in-house dengue IgM enzyme-linked immunoassays routinely performed by each of the selected centres. Known positive and negative dengue specimens, as well as specimens from non-dengue cases, were included in the evaluation. Results: Based on 402 specimens tested by the six centres, the sensitivity was 92.1 and specificity 88.1, with an overall agreement of 92.8 when compared with IgM EIA assays performed on microplates. Conclusions: The results suggest that this commercial kit has a role to play in the diagnosis of dengue infection, especially in peripheral hearth settings. (C) 1996 Elsevier Science B.V.